2022
DOI: 10.1177/10732748221107590
|View full text |Cite
|
Sign up to set email alerts
|

PD-1/L1 With or Without CTLA-4 Inhibitors Versus Chemotherapy in Advanced Non-Small Cell Lung Cancer

Abstract: Background With the use of immune-checkpoint inhibitors (ICIs) in advanced or metastatic non-small cell lung cancer (NSCLC), whether ICIs or chemotherapy is more effective still remains controversial. This study was conducted to evaluate the efficacy of programmed cell death 1 (PD-1), programmed cell death ligand 1 (PD-L1), cytotoxic T-lymphocyte protein 4 (CTLA-4) alone or in their combination vs chemotherapy in patients with advanced or metastatic NSCLC. Methods This meta-analysis was conducted from PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Several studies have reported a correlation between higher TMB and ICI efficacy, indicating that TMB could serve as a reliable predictive biomarker. 38 , 40 , 41 , 42 This study examines the correlation between RFC4 expression and TMB and MSI levels based on TCGA data. The results indicate that RFC4 expression is correlated with TMB and MSI levels in BLCA, COAD, KICH, KIRC, LGG, LUAD, PRAD, READ, SKCM, STAD and UCEC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported a correlation between higher TMB and ICI efficacy, indicating that TMB could serve as a reliable predictive biomarker. 38 , 40 , 41 , 42 This study examines the correlation between RFC4 expression and TMB and MSI levels based on TCGA data. The results indicate that RFC4 expression is correlated with TMB and MSI levels in BLCA, COAD, KICH, KIRC, LGG, LUAD, PRAD, READ, SKCM, STAD and UCEC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TMB can serve as a reliable indicator of the effectiveness of ICI, and tumours with higher TMB are more likely to respond favourably to cancer immunotherapy. Several studies have reported a correlation between higher TMB and ICI efficacy, indicating that TMB could serve as a reliable predictive biomarker 38,40–42 . This study examines the correlation between RFC4 expression and TMB and MSI levels based on TCGA data.…”
Section: Discussionmentioning
confidence: 99%
“…ICIs can block the negative costimulatory signalling pathway of T cells, thereby improving the body’s antitumour immune response and promoting the clearance of T cells to tumour cells ( 11 , 12 ). At present, ICIs that are mainly used in clinical practice include cytotoxic T-lymphocyte associated protein 4 (CTLA-4) inhibitors, programmed cell death 1 (PD-1) inhibitors and programmed cell death ligand 1 (PD-L1) inhibitors ( 13 ). ICIs targeting CTLA-4 and PD-1/PD-L1 can block the immune checkpoint pathway to restore the body’s antitumour immune response and exert antitumour effects.…”
Section: Introductionmentioning
confidence: 99%